2021
DOI: 10.1097/md.0000000000027828
|View full text |Cite
|
Sign up to set email alerts
|

Health care costs associated with clinic visits for prevention of mother-to-child transmission of HIV in Dar es Salaam, Tanzania

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(73 reference statements)
1
1
0
Order By: Relevance
“…A large preponderance of these costs was driven by consumables that included medications and labs (61–91% of total costs), followed by human resources (3–22%), indirect costs (2–14%), and space and equipment (1–2%). Our observed pattern of costs is consistent with prior research, including in Tanzania [ 23 25 ]. We also observed that costs varied widely across individuals, facilities, and service lines, and that these were partially explained by patient- and facility-level characteristics.…”
Section: Discussionsupporting
confidence: 92%
“…A large preponderance of these costs was driven by consumables that included medications and labs (61–91% of total costs), followed by human resources (3–22%), indirect costs (2–14%), and space and equipment (1–2%). Our observed pattern of costs is consistent with prior research, including in Tanzania [ 23 25 ]. We also observed that costs varied widely across individuals, facilities, and service lines, and that these were partially explained by patient- and facility-level characteristics.…”
Section: Discussionsupporting
confidence: 92%
“…Implementing EUDC by providing psychoeducation and counseling may also have decreased symptoms in both intervention and control sites. Specific to this population, it is also possible that at the second follow-up (mean 11 months postpartum), women knew their infants’ HIV test results (which, while not testable in our study population, given the low rates of mother-to-child transmission in Dar es Salaam [ 38 ], were predominantly negative), which may have decreased stress and subsequently reduced depressive symptom severity in both groups. Particularly in resource-constrained settings, this evidence of a large reduction in depressive symptoms in the control group may suggest the need for better targeting of women with depression during the antenatal and early postpartum period when this intervention had the strongest effect.…”
Section: Discussionmentioning
confidence: 99%